The transition from Modeling to modeling in the Middle School context - Barbosa, Fábio Henrique (2019)
The content of the scientific article aims to present the experience of a undergraduate student involved, on the one hand, with mathematical modeling and, on the other hand, with modeling from the perspective of a teaching proposal. The research problem involved the issue of inadequate disposal of cooking oil and environmental implications. With regard to mathematical modeling we present the analysis of one of the experiments performed by the first author. The modeling was based on the planning of a teaching proposal based on mathematical contents predicted for the third grade of High School. In the transition between modeling and modeling, in terms of school content, we have established connections between mathematical and statistical graphs. Data collection and processing of information is intended to raise awareness about the need to get into the habit of disposing of and / or reusing cooking oil properly.